Surgical outcomes and complications following distal biceps tendon reconstruction: a systematic review and meta-analysis - Madison L. Litowski, MD; Jennifer Purnell, MD; Kevin A. Hildebrand, MD, FRCSC; Aaron J. Bois, MD, MSc, FRCSC (JSES International, 2021)
Background: Primary repair of chronic distal biceps tendon ruptures may not be possible because of tendon retraction, and there remains no clear consensus on the type of reconstruction technique used. The purpose of this study was to report the clinical outcomes and complication rates following reconstruction of chronic distal biceps tendon ruptures. Methods: A systematic review was performed following PRISMA guidelines. The following databases were searched: Embase, MEDLINE, and Cochrane Central Register of Controlled Trials. The primary outcomes of interest included range of motion, strength, and functional outcome scores. Secondary outcomes included complication, reoperation, and revision rates. Outcomes and complication rates of each graft type and fixation technique were aggregated and compared with nonparametric Wilcoxon signed rank and rank sum tests. Spearman rank coefficients were calculated for time from injury to surgery on all outcomes. Results: There were no significant differences found between the graft type or fixation technique for postoperative range of motion, strength, and patient-reported outcomes. Postoperative complications were substantially higher in the autograft group (34%) as compared to the allograft group (14%). The fixation technique used also demonstrated a significantly increased complication rate in the weave group compared with the onlay group (34% and 9%, respectively). Conclusion: Our results do not reveal any statistically significant differences between groups in the primary outcomes. However, substantially higher complication rates were observed in the autograft and weave cohorts; more than half of the complications related to the use of autograft were associated with donor site morbidity. No specific graft type was identified as superior, although this may be due to the small patient numbers included within this study.